Adolescent’ Experiences Using Pornography - Mariyati Mariyati; Eva Zuliana; Arifianto Arifianto (GLOBAL HEALTH SCIENCE GROUP, 2021)
The experience of teenagers using pornography in Semarang City has greatly increased. Many teenagers don’t understand what the harm use pornography harm. The impacts that occur include difficulty concentrating, not focusing while studying, daydreaming, hallucinations, increased sexual appetite with masturbation and masturbation. Adolescents become more precocious and they had sex before marriage. This study aims to explore the experiences of adolescents who access pornography at SMA Setia Budhi Semarang City. The sampling technique used purposive sampling to determine the appropriate sample, namely adolescents who accessed pornographic media for more than 2 months. This type of research is qualitative with a descriptive phenomenology approach. Obtained data saturation in the fifth participant. Data collection through in-depth interviews (in depth interviews) and field notes (field notes). Researcher's data analysis was carried out after and during the study and the validity of the data by using member checking. This study resulted in 4 themes, namely the supporting factors for adolescents in using pornography, increasing the frequency of using pornography, the response of adolescents when using pornography, and the perceived impact of using pornography. The main reason why teenagers access pornography is due to the invitation of their friends and their own desires, so that the desire to access pornography appears continuously. This results in adolescents having difficulty concentrating, learning problems, difficulty sleeping and the desire to try and imitate seen sexual behavior.